Carotenoids in Butter from Canistel (Pouteria campechiana) - Puspita, Dhanang (University of Brawijaya, 2019)
The purpose of this study was to produce butter from canistel fruit and see the carotenoid content. The method used is butter production, sensory analysis, and carotenoid analysis. Butter production is made with 2 different formulations by comparing fruit extracts and whipping cream: mentega-1 (1: 3.5), and mentega-2 (1: 1.5). Sensory testing involving 53 untrained panelists by providing parameters; taste, aroma, color, texture, and overall. The results of the study, canistel fruit can be made into butter with 2 variants. Organoleptic test results, overall the panelists liked control butter, while for the color and aroma of the panelists liked mentega-2. The content of carotenoids in canistel was 278, 24 µg/g, mentega-1 was 95.99 µg / g, and mentega-2 was 112.35 µg/g. Carotenoid content in butter from canistel can be used as intake of vitamin A. It can be concluded that for canistel can be used as butter and contains carotenoids to the needs of vitamin A.